2012
DOI: 10.1016/j.devcel.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Neurogenesis from Neural Progenitor Cells Requires Injury-Induced Expression of Gata3

Abstract: The adult zebrafish brain, unlike mammalian counterparts, can regenerate after injury owing to the neurogenic capacity of stem cells with radial glial character. We hypothesized that injury-induced regenerative programs might be turned on after injury in zebrafish brain and enable regenerative neurogenesis. Here we identify one such gene-the transcription factor gata3-which is expressed only after injury in different zebrafish organs. Gata3 is required for reactive proliferation of radial glia cells, subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(161 citation statements)
references
References 30 publications
4
156
1
Order By: Relevance
“…Neuroinflammation and immune cells including microglia, regenerative astrocytes, and leukocytes have emerged as factors regulating injury-induced neurogenesis (for review, see Kohman and Rhodes, 2013). After neuronal death, microglia migrate to the injury site to remove cell debris, whereupon they release proinflammatory cytokines and proproliferative factors (for review, see Smith et al, 2012;Chen et al, 2013) to promote regeneration (Molowny et al, 1995;Kizil et al, 2012). Thus, a neuroinflammatory response may mediate apoptotic neuron clean up during HVC regression and may promote the vVZ proliferation increase we observed.…”
Section: Abmentioning
confidence: 93%
“…Neuroinflammation and immune cells including microglia, regenerative astrocytes, and leukocytes have emerged as factors regulating injury-induced neurogenesis (for review, see Kohman and Rhodes, 2013). After neuronal death, microglia migrate to the injury site to remove cell debris, whereupon they release proinflammatory cytokines and proproliferative factors (for review, see Smith et al, 2012;Chen et al, 2013) to promote regeneration (Molowny et al, 1995;Kizil et al, 2012). Thus, a neuroinflammatory response may mediate apoptotic neuron clean up during HVC regression and may promote the vVZ proliferation increase we observed.…”
Section: Abmentioning
confidence: 93%
“…These unexpected findings have revealed that distinct mechanisms control neurogenesis in intact and injured brains. A recent study using zebrafish has shown that injury-induced GATA3 plays a crucial role in regenerating neurons lost to insult (Kizil et al 2012). A similarity between GATA3 in zebrafish and Gsx2 in mice is that both are broadly up-regulated by injury and are essential for stimulation of neurogenesis.…”
Section: Mechanisms For Injury-induced Neurogenesismentioning
confidence: 99%
“…Zebrafish are highly regenerative as adults, being equipped to regrow tissues such as amputated fins, injured retinae, transected optic nerves and spinal cord, lost heart muscle, brain, hair cells, pancreas, liver, skeletal muscle and kidney (Johnson and Weston, 1995;Bernhardt et al, 1996;Becker et al, 1997;Vihtelic and Hyde, 2000;Poss et al, 2002;Sadler et al, 2007;Ma et al, 2008;Jacoby et al, 2009;Moss et al, 2009;Diep et al, 2011;Andersson et al, 2012;Goldshmit et al, 2012;Kizil et al, 2012). Adult zebrafish present advantages for mechanistic studies as they are small, easy to raise in large numbers and accessible to cell transplantation and molecular genetic manipulations.…”
Section: Introductionmentioning
confidence: 99%